The Dynamics of Mastering Multi-Foreign Languages: A Polyglot's Perspective - Nisa, Ihda Khairun; Dzulfikri, Dzulfikri (ENGLISH FRANCA : Academic Journal of English Language and Education, 2023)
The dynamics and challenges in mastering multiple foreign languages often need to be more detailed, especially from a polyglot's perspective. Therefore, this research aims to analyze the dynamics of mastering multiple foreign languages from the viewpoint of a polyglot who can communicate in six foreign languages. This research is expected to provide insight and inspiration for those who want to become a polyglot. This type of research is qualitative research with a descriptive method. The researcher collects data by interviews. The research subject is a polyglot who is 28 years old, mastering six foreign languages, consisting of Arabic, English, Korean, Chinese, Japanese, and German. The research concluded that the dynamics of mastering multiple foreign languages by a polyglot involve intrinsic motivation factors, consistency and determination, strategic approaches to learning, and strategies to maintain and expand mastery of foreign languages. Polyglot's obstacles in learning foreign languages include cognitive, psychological, and social aspects. However, these polyglots can respond to these challenges with proactive and ongoing strategies to strengthen and deepen their language fluency. This study is expected to provide a deeper understanding of the dynamic process of mastering multiple foreign languages from the perspective of a polyglot.